(3GdQSGdI GdbTjQjI aj GdJUhas - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s ((3GdMSjf Hf eMeO Hf GdMSjf GdYdhi GdGQehi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HLdGd edchJg CeG HYO QVi Gddg Yfce abO LYd Gddg gPg GdWGFaI UahI ChdjGFg haVdge Ydi GdcGaI ef YHGOg HYO QSdg hCfHjGFg UdhGJ Gddg Ydjge s
(3BNQgG (B:s
(3hCgd GdUaG jNQLhf GdNdb hGdeYGQa ef GdbdH JMbbkG HGddg YR hLd agPg hUjJfG Edi GdeDjOjf fSFd Gdgd GdcQje dge GdJhajb hEf dGjLYdgG hHGdkG YdjfkG bO fLR cJGH GdQSGdI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B882s
Keywords: (3GdJUha hGdBOGH GdTQYjIs